Al-Khalīlayn in Arabic Literary Romanticism - Yusuf Haikal (Sekolah Tinggi Agama Islam Darul Ulum Banyuanyar Pamekasan, 2021)
This article aims to provide an overview of romanticism in Arabic literature, in particular through two important figures in this school. important in the foundation and development of romanticism in Arabic literature. The method used in this article is descriptive qualitative and literature study. This study also uses the technique of observing and taking notes in data collection. From the discussion it can be concluded that the flow of romanticism is one of the popular streams that first appeared in the 18th century in Europe and entered the Arab region at the beginning of the 20th century. The entry of romanticism into the Arab world was pioneered by Khalīl Muthran. Apart from Khalīl Muthran, there is another Arabic literary figure who popularized this romanticism, namely Khalīl Gibran. These two Khalīls were important figures in the emergence and development of romanticism in Arabic literature. This can be seen from the life history of both of them who both studied literature in western countries. In addition, the works produced by these two figures show a strong romantic style, which strengthens the character of the two in Arabic literary romanticism